Fostering critically reflective thinking with first-year university students: early thoughts on implementing a reflective assessment task. Issue 4 (3rd July 2020) - Procter, Lesley
ABSTRACT: Critical reflective thinking is a staple of desirable graduate outcomes worldwide, but is notoriously difficult to foster, especially in first-year undergraduate students. Students often doubt their ability to think beyond the perspectives and information delivered to them during class time. They may be reluctant to risk their personal thoughts and opinions, especially when those perspectives may be judged in the marking process. Attempting to foster critical reflective thinking skills in large classes may be particularly difficult where, in addition to class size, teaching staff face intersecting challenges at an institutional level as well as with different student cohorts. This paper presents one learning initiative introduced to generate critical reflective analysis and situates it in relation to learning and teaching literature. Students were asked to identify the main points in each of three course blocks, find an image they felt represented those points, and analyse their choice. These reflections formed part of a workbook students kept throughout the semester. This paper also discusses the decisions involved in designing this task and offers some evaluative comments on the strengths and perceived weaknesses of the task design.